Prevalence of coronaryheart disease risk factors among fisherman in Tumpat, Kelantan, 1994 - Norazmi Abdullah; Md Idris Mohd Nor (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Coronary heart disease (CHD) is the most common cause of death in developed and developing countries including Malaysia. High prevalence of CHD occurs amongst those who have risk factors especially smoking, hypertension, diabetes mellitus, taking fatty food and abnormality of blood lipid levels. Fishermen had low prevalences of CHD risk factors and low incidence of IHD. A cross-sectional study was done amongst 223 persons consist of fishermen (n=176) and non fishermen (n=51) in Tumpat Kelantan. The response rate was 75.6% and 70.8% respectively. The main objective of the study is to determine the prevalence of CHD risk factors and the association with age and social economic status and also to compare with non-fishermen. Fishermen had low social economic status. Prevalence of poverty was 71.4% and 36.8% had no formal education(p<0.05) .Three main risk factors found to be high were smoking (76.5%), HDL-cholestrol <35mg/dl (95.8%) and hypertension (28.8%) .All these 3 factors were high amongst fishermen. Prevalence of overweight was associated with income level and Body mass index was positively correlated with protein intake, diastolic and systolic blood pressure and triglyseride (p<0.05) .Mean diastolic blood pressure in fishermen was lower amongst smokers as compared to non-smoker. The prevalence of diabetes mellitus was significantly higher amongst older age group. Prevalences of hypertension, hypertriglyceridemia, hypercholestrolemia, hyperLDL-cholestrolemia and hypoHDLcholestrolemia were not associated with age and social economic status. Overall calorie intake was lower in both groups except protein. Fishermen's calorie and protein intake were lower as compared to non fishermen. It's were statistically significant. 46.6% fishermen had 2 and only 24.1% had 3 or more risk factors as compared to non fishermen's 33.3% and 33.3% respectively. Only 8.3% fishermen and 15.2% non fishermen did not have risk factors. There was difference in number of risk factors according to age group (p<0.05) .